Pembelajaran Sosiologi Secara Daring Selama Pandemi Covid-19 - Syahrul, Syahrul; Yusuf, Nur Wahida; Yayuk Julyyanti; Nautu, Albert K.; Arifin (Jurnal Penelitian dan Pendidikan IPS, 2023)
This study aims to find out about online sociology learning during the COVID-19 pandemic at SMA N 1 Taebenu. This research was qualitative research that was intended to deeply understand the effectiveness of online sociology learning during the COVID-19 pandemic. The subjects of this study were students, teachers, and the headmaster. The data collection used observation, interviews, and documentation. Interactive analysis techniques include data reduction, data display, and drawing conclusions. The results of research that implementing online learning during the COVID-19 pandemic was not effective because in the learning process students and teachers experienced obstacles by teachers experiencing limitations in the use of learning platform (technology). Then the obstacles experienced by students were their limitations in facilities such as not having a cellphone, laptop, also not having an internet package, and being constrained by the internet connection